Conservation of the Ca2+-permeability through the voltage sensor domain of mammalian CatSper subunit. Issue 1 (1st January 2018) - Arima, Hiroki; Tsutsui, Hidekazu; Okamura, Yasushi
ABSTRACT: Cation channel of Spermatozoa (CatSper) is one of the voltage-gated ion channels consisting of voltage sensor domains (VSDs) and pore-gate domains. CatSper is exclusively expressed in spermatozoa and indispensable for Ca 2+ influx into cytosol. Recently, we have reported that the VSD of ascidian CatSper induces Ca 2+ -permeable pathways in heterologous expression systems. However, it is not known whether ion permeability through the VSD of CatSper is conserved in mammals. In the present study, electrophysiology and fluorometry in Xenopus oocytes revealed that Ca 2+ -permeable paths are also formed by expressing the VSD of murine CatSper. We also examined the permeability to monovalent cations other than Na + in the VSD of ascidian CatSper.